2004
DOI: 10.1080/14992020400050043
|View full text |Cite
|
Sign up to set email alerts
|

Near-threshold recordings of amplitude modulation following responses (AMFR) in children of different ages

Abstract: Amplitude modulation following responses (AMFR) to single near-threshold 40-Hz or 80-Hz amplitude-modulated tones of 1 kHz were recorded in 48 normal children between the ages of 2 months and 14 years. Children under the age of 2 years were tested during natural sleep, and older children were tested awake. The objectives of this study were to find out how the AMFR changes with age and to determine the most effective modulation frequency for objective threshold assessment at different ages. The optimal modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…The maturational period of responses to higher rates is known to be shorter than the maturational period of lower rates. While responses in the frequency domain of 4, 20 and 40 Hz have been demonstrated to significantly differ between children and adults, responses to 80 Hz have been thought to change little with age (Pethe et al, 2004;Tlumak et al, 2012). However, a recent study showed that the maturational period for such higher rates would be more prolonged than initially assumed (Skoe et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…The maturational period of responses to higher rates is known to be shorter than the maturational period of lower rates. While responses in the frequency domain of 4, 20 and 40 Hz have been demonstrated to significantly differ between children and adults, responses to 80 Hz have been thought to change little with age (Pethe et al, 2004;Tlumak et al, 2012). However, a recent study showed that the maturational period for such higher rates would be more prolonged than initially assumed (Skoe et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Some researchers report that responses are greater when tones are modulated at 20 Hz (Fifer, 1985;Suzuki & Kobayashi, 1984), while others report responses to be higher in amplitude between 25 and 40 Hz (Pethe et al, 2004;Riquelme et al, 2006), or between 72 and 97 Hz (Aoyagi et al, 1993(Aoyagi et al, , 1994Pethe et al, 2004;Rickards et al, 1994). Still others have reported no consistent amplitude peak when tones were modulated at frequencies between 9 and 59 Hz (Stapells et al, 1988).…”
mentioning
confidence: 89%
“…Taking into account the results of the present study and of Savio et al [2001], this could indicate that the largest increase in SNR takes place in the fi rst year of life. However, the SNRs in the study of Pethe et al [2004] were in general very low, partly caused by the very short test duration and high noise levels.…”
Section: Age-related Changes In Assrmentioning
confidence: 99%
“…However, both studies have observed an age-related change in ASSR, although in different subject groups. Pethe et al [2004] tested children between the ages of 2 months and 14 years with the singlefrequency ASSR. At 50 dB nHL, the amplitude slightly increased with age, but the increase in SNR was not signifi cant.…”
Section: Age-related Changes In Assrmentioning
confidence: 99%